Public health and economics: a marriage of necessity - Alan Maynard (SAGE Publishing, 2012)
With resources always scarce limited resources have to be targeted at those interventions, prevention and cure, that give the greatest population health gain at least cost. Mere identification of what works in prevention is inadequate unless this evidence is supplemented with economic analysis that identifies what is cost effective. Public health without the use of economics is incomplete.